Gutenberg in Shanghai : Chinese Print Capitalism, 1876-1937 - Reed, Christopher A. (Christopher Alexander), 1954- (Book collections on Project MUSE., 2004)
In the mid-1910s, what historians call the "Golden Age of Chinese Capitalism" began, accompanied by a technological transformation that included the drastic expansion of China's "Gutenberg revolution." Gutenberg in Shanghai is a brilliant examination of this process. It finds the origins of that revolution in the country's printing industries of the late imperial period and analyzes their subsequent development in the Republican era. Under diverse social, political, and economic influences, this technological and cultural revolution saw woodblock printing replaced with Western mechanical processes. This book, which relies on documents previously unavailable to both Western and Chinese researchers, demonstrates how Western technology and evolving traditional values resulted in the birth of a unique form of print capitalism whose influence on Chinese culture was far-reaching and irreversible. Its conclusion contests scholarly arguments that view China's technological development as slowed by culture, or that interpret Chinese modernity as mere cultural continuity. A vital reevaluation of Chinese modernity, Gutenberg in Shanghai will app.